2018
DOI: 10.1111/joa.12884
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and immunohistochemical study of the rabbit vomeronasal organ

Abstract: The characterization of the rabbit mammary pheromone, which is sensed by the main olfactory system, has made this species a unique model for the study of pheromonal communication in mammals. This discovery has brought attention to the global understanding of chemosensory communication in this species. Chemocommunication is mediated by two distinct organs located in the nasal cavity, the main olfactory epithelium and the vomeronasal organ (VNO). However, there is a lack of knowledge about the vomeronasal system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 69 publications
(129 reference statements)
5
53
0
Order By: Relevance
“…1 and 4). This topography is only comparable to that described in rabbits 51 , where the organs rest over a prominence of the vomer bone. Two patterns of communication of the vomeronasal duct with the outside have been described.…”
Section: Discussionsupporting
confidence: 54%
“…1 and 4). This topography is only comparable to that described in rabbits 51 , where the organs rest over a prominence of the vomer bone. Two patterns of communication of the vomeronasal duct with the outside have been described.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, the same authors noted an asymmetric muscle layer around the vomeronasal duct, namely the lateral thicker wall and medial thinner wall; the former displayed a very large amount of nerves with NOS-immunoreactivity (possibly cholinergic), while the latter showed a predominant NPY-immunoreactivity (possibly adrener-differing according to the location at the rostro-caudal axis. Based on figures presented in the literature, rabbits appear to possess the most developed vascular system, composed of grouped blood vessels with large diameters (Villamayor et al, 2018), being comparable to the mouse VNO examined in the present study. In contrast, animals like the opossum, cat, and wallaby do not have such advanced venous sinuses around non-sensory epithelium (Salazar et al, 1996;Poran, 1998;Schneider et al, 2008).…”
Section: Characteristics Of Vasculaturesupporting
confidence: 79%
“…Stimulus substances must be forced into the organ by auxiliary devices rather than simple diffusion via the narrow entrance duct. The spongy tissue containing the developed vasculature is a kind of erectile tissue similar to the penis and functions to pump in or out the luminal contents of the vomeronasal duct (Meredith et al, 1980;Eccles, 1982;Villamayor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When Gαi2 and Gαo protein expression has been observed in rodents, such as the rat, two distinct zones were observed: an apical layer of neurosensory cells, which was immunopositive for anti-Gαi2 antibodies, and a basal layer, which was immunopositive to anti-Gαo antibodies (Halpern et al, 1998). In the fox, as in the rabbit (Villamayor et al, 2018), two distinct interspersed patterns were observed for the immunopositivity of both Gα proteins in the fox, which may be associated with two distinct subpopulations of neuroreceptor cells in the sensory epithelium of the VNO.…”
Section: Immunohistochemical Expression Of G Proteins Alpha-subunitsmentioning
confidence: 99%